2018
DOI: 10.18203/2320-6012.ijrms20184407
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of breast cancer and its risk factors among Al-Quds university students in Palestine

Abstract: Background: Cancer is a major public health problem globally. The incidence of cancer is escalating rapidly in many low- and middle-income countries like Palestine due to the epidemiological transition. This could be due to lack of awareness, knowledge and beliefs about breast cancer and its management among females. Aims and objectives was to determine knowledge of breast cancer risk factors, symptoms and early detection methods among Al-Quds University female students.Methods: A descriptive cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
3
5
0
Order By: Relevance
“…Moreover, the outcome isn't consistent with another study, which is done in Al-Quds university -Palestine for non-health related disciplines which showed there is poor knowledge about BC risk factor, signs risk, and prognosis of the disease. 23 This study showed good knowledge about early detection techniques, mammography, U/S, and CBE, which is consistent with previous studies. However they have poor practice for mammogram to detect BC.…”
Section: Disscusionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the outcome isn't consistent with another study, which is done in Al-Quds university -Palestine for non-health related disciplines which showed there is poor knowledge about BC risk factor, signs risk, and prognosis of the disease. 23 This study showed good knowledge about early detection techniques, mammography, U/S, and CBE, which is consistent with previous studies. However they have poor practice for mammogram to detect BC.…”
Section: Disscusionsupporting
confidence: 92%
“…The results of our study showed that the students have a great knowledge about the signs risk factors and bad effect of BC on their lives. Moreover, the outcome isn't consistent with another study, which is done in Al‐Quds university ‐Palestine for non‐health related disciplines which showed there is poor knowledge about BC risk factor, signs risk, and prognosis of the disease 23 . This study showed good knowledge about early detection techniques, mammography, U/S, and CBE, which is consistent with previous studies.…”
Section: Disscusionsupporting
confidence: 60%
“…Another study recently conducted in Gaza and published showed poor recognition of cancer symptoms in general among adolescents and adult participants; however, their knowledge about cancer risk factors is good [24]. Additionally, the result is not in line with another study conducted in the Al-Quds University, Palestine, which included students from non-health-related disciplines showed poor identification of risk factors, signs, and symptoms of BC [25]. e difference in the findings of the current study and the previous studies is related to the different target populations as our participants' knowledge increased mainly because of their learning curriculum in the Faculty of AMS, and this supports another finding in this study that the most common sources of their information were derived from their university studies.…”
Section: Discussionmentioning
confidence: 80%
“…Another study is a master thesis study conducted in Gaza to assess the knowledge and practice BSE among nurses working at the primary healthcare centers, which showed a good knowledge about BC early detection methods, CBE, and mammography; however, their mammography practices were low [26]. In addition, [25] revealed a good knowledge about early detection methods of BC such as mammography and U/S. e majority of participants heard about BSE and recognized that it is useful in early detection of BC disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation